Trophic ecology of benthic fish assemblages in a lowland river in the Brazilian Amazon - Duarte, Cleber; Magurran, Anne E.; Zuanon, Jansen; Deus, C. P. (Aquatic Ecology, 2019)
Studies on the trophic ecology of fish have revealed considerable alimentary plasticity for the majority of ichthyofauna in tropical rivers. This leads to the prediction that diet reflects the availability of food in the environment, namely seasonal variation in the abundance and type of food resources. To examine this, we assess: (1) seasonal variation in the diet and trophic structure of assemblages of benthic fish inhabiting the main channel of a large floodplain river in the Brazilian Amazon, (2) seasonal changes in the availability of food resources, (3) the trophic response (food selectivity) of benthic species in relation to food availability and (4) niche overlap among benthic species. Data were collected during 2 rising and 2 receding phases. Aquatic insects, plant matter and detritus were the predominant items in the diet of assemblages of benthic fish. The majority of fish species changed their diet between seasons. The diets of Exallodontus aguanai and Sternarchella calhamazon were studied in detail and showed positive correlation with food resource availability. Feeding selectivity varied among seasons for these two species. Niche overlap between these two species was observed during only one receding season. Our results reveal the importance of aquatic insects in the predominantly omnivorous diet of the benthic fish assemblages. Trophic plasticity was also evident, possibly because of the seasonal availability of food items. These results underline the role that organic matter derived from floodplains plays in this aquatic system which is characterised as having naturally low autochthonous productivity. © 2019, Springer Nature B.V.
Keywords: Hexapoda; Sternarchella